The Influence of Social Media on High School Students' Mathematics Learning Achievement: Analysis of Phase-E Students - Sindi Aulia; Linda Rohmatul Maula; Moh. Syadidul itqan; Rasmus Lindholm (CV Edujavare Publishing, 2024)
Social media is often used to communicate, share information, and fill free time. Its use can affect student learning achievement, with varying impacts depending on the context and research method. The purpose of this study is to conduct an in-depth analysis related to the influence of social media use on students' mathematics learning achievement in phase-E at SMA Negeri 1 Gamping. In its implementation, this study involved 30 students selected as a sample to represent the population. This study uses a quantitative approach with a correlational method to reveal the relationship between the intensity of social media use and students' mathematics learning outcomes in more detail and objectively, the results of the analysis show a significant relationship between social media use and student learning achievement, with a calculated t value > t table (21.771 > 2.048) and a sig. value of 0.000 < 0.05. This indicates that the use of social media has an impact on students' mathematics learning achievement